Escovopsioides as a fungal antagonist of the fungus cultivated by leafcutter ants - Osti, Julio Flavio [UNESP] (2018)
Background: Fungus gardens of fungus-growing (attine) ants harbor complex microbiomes in addition to the mutualistic fungus they cultivate for food. Fungi in the genus Escovopsioides were recently described as members of this microbiome but their role in the ant-fungus symbiosis is poorly known. In this study, we assessed the phylogenetic diversity of 21 Escovopsioides isolates obtained from fungus gardens of leafcutter ants (genera Atta and Acromyrmex) and non-leafcutter ants (genera Trachymyrmex and Apterostigma) sampled from several regions in Brazil. Results: Regardless of the sample locality or ant genera, phylogenetic analysis showed low genetic diversity among the 20 Escovopsisoides isolates examined, which prompted the identification as Escovopsioides nivea (the only described species in the genus). In contrast, one Escovopsioides isolate obtained from a fungus garden of Apterostigma megacephala was considered a new phylogenetic species. Dual-culture plate assays showed that Escovopsioides isolates inhibited the mycelium growth of Leucoagaricus gongylophorus, the mutualistic fungus cultivated by somes species of leafcutter ants. In addition, Escovopsioides growth experiments in fungus gardens with and without ant workers showed this fungus is detrimental to the ant-fungus symbiosis. Conclusions: Here, we provide clues for the antagonism of Escovopsioides towards the mutualistic fungus of leafcutter ants.